Pain assessment practices in Swedish and Norwegian neonatal care units. Issue 3 (28th December 2017) - Andersen, Randi Dovland; Munsters, Josanne M.A.; Vederhus, Bente Johanne; Gradin, Maria
Abstract : Background: The use of measurement scales to assess pain in neonates is considered a prerequisite for effective management of pain, but these scales are still underutilised in clinical practice. Aim: The aim of this study was to describe and compare pain assessment practices including the use of pain measurement scales in Norwegian and Swedish neonatal care units. Methods: A unit survey investigating practices regarding pain assessment and the use of pain measurement scales was sent to all neonatal units in Sweden and Norway (n = 55). All Norwegian and 92% of Swedish units responded. Results: A majority of the participating units (86.5%) assessed pain. Swedish units assessed and documented pain and used pain measurement scales more frequently than Norwegian units. The most frequently used scales were different versions of Astrid Lindgren's Pain Scale (ALPS) in Sweden and Echelle Douleur Inconfort Noveau‐Ne (EDIN), ALPS and Premature Infant Pain Profile (PIPP) in Norway. Norwegian head nurses had more confidence in their pain assessment method and found the use of pain measurement scales more important than their Swedish colleagues. Conclusion: The persisting difference between Swedish and Norwegian units in pain assessment and the use of pain measurement scales are not easily explained. However, the reported increased availability and reported use of pain measurement scales in neonatal care units in both countries may be seen as a contribution towards better awareness and recognition of pain, better pain management and potentially less suffering for vulnerable neonates.